2014
DOI: 10.1007/s00198-014-2693-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 18-month low-magnitude high-frequency vibration on fall rate and fracture risks in 710 community elderly—a cluster-randomized controlled trial

Abstract: LMHFV is effective in fall prevention with improved muscle strength and balancing ability in the elderly. We recommend its use in the community as an effective fall prevention program and to decrease related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(141 citation statements)
references
References 29 publications
2
129
0
10
Order By: Relevance
“…2 )] and frequency ranged from 20 to 90 Hz (Bemben et al, 2010;Fuermaier et al, 2014;von Stengel et al, 2011), is also reported to have positive effects on osteogenic differentiation and osteogenesis (Dumas et al, 2010;Kim et al, 2012;Leung et al, 2014;Luu et al, 2009). Some previous studies using LMHFV for fracture healing in rats report its promising effects on callus formation, mineralisation and bone remodelling (Chow et al, 2011;Leung et al, 2009;Shi et al, 2010).…”
Section: The Effect Of Whole Body Vibration On Fracture Healing -A Symentioning
confidence: 99%
See 1 more Smart Citation
“…2 )] and frequency ranged from 20 to 90 Hz (Bemben et al, 2010;Fuermaier et al, 2014;von Stengel et al, 2011), is also reported to have positive effects on osteogenic differentiation and osteogenesis (Dumas et al, 2010;Kim et al, 2012;Leung et al, 2014;Luu et al, 2009). Some previous studies using LMHFV for fracture healing in rats report its promising effects on callus formation, mineralisation and bone remodelling (Chow et al, 2011;Leung et al, 2009;Shi et al, 2010).…”
Section: The Effect Of Whole Body Vibration On Fracture Healing -A Symentioning
confidence: 99%
“…Some studies provide evidence that WBV has effects on the musculoskeletal system, including improving muscle function (Rees et al, 2008;Sitja-Rabert et al, 2015), increasing bone mineral density (BMD) (Lam et al, 2013;Verschueren et al, 2004), reducing risks of falls and improving muscle strength and balancing ability . Low-magnitude high-frequency vibration (LMHFV), a type of WBV with magnitude usually lower than 1 ×g [magnitude, in gravitational acceleration (m/s2 )] and frequency ranged from 20 to 90 Hz (Bemben et al, 2010;Fuermaier et al, 2014;von Stengel et al, 2011), is also reported to have positive effects on osteogenic differentiation and osteogenesis (Dumas et al, 2010;Kim et al, 2012;Leung et al, 2014;Luu et al, 2009). Some previous studies using LMHFV for fracture healing in rats report its promising effects on callus formation, mineralisation and bone remodelling (Chow et al, 2011;Leung et al, 2009;Shi et al, 2010).…”
mentioning
confidence: 99%
“…Among them, the vibration therapy has emerged over the last decades as a promising non-invasive treatment for osteoporosis. In fact -through a mechanism not yet univocally clarified -high-frequency vibratory stimulation is able to significantly stimulate osteogenesis in animal models (11)(12)(13)(14), and studies in human indicate that it improves bone mineral density (BMD), muscle strength and proprioception, particularly in people with osteoporosis or those with motor impairment from neuromuscular diseases of various etiologies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The aim of this study is to evaluate the effect of combined treatment with focused mechano-acoustic vibration and pharmacological therapy on BMD and muscle strength in post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…(16) In another study of 710 post-menopausal women, using low-magnitude high-frequency vibration (LMHFV) for 18 months, the author stated that the BMD of the hip and spine showed a positive trend in the vibration group compared to the controls (mean between-group difference 1.43% for femoral neck, 1.12% for spine) (22). The author concluded that the effect was not statistically significant after Bonferroni adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] it was found that there was an increase in BMD after different amounts of WBV exposure. In some studies whose primary outcomes were body balance and muscle strength, the authors observed positive effects of WBV therapy on those outcomes (17,21).…”
Section: Limitations Suggestions and Conclusionmentioning
confidence: 99%